Curcuma longa as an anti-carcinogen: A literatura review - Pinzón, Stefanía; Cabrera, Lucía; Pico-Fonseca, Sayda Milena (Universidad y Salud, 2023)
Introduction: Curcuma longa (turmeric) is a plant of Hindu origin that is mainly composed of curcumin and has many attributes, including hypolipidemic, antioxidant, anti-inflammatatory and anticancer properties. Objective: To determine whether turmeric has anticancer properties, based on scientific evidence. Materials and methods: A literature review of PubMed, MEDLINE and Scielo databases was conducted. The review covered the first semester in 2006 to first semester of 2018 time period. Results: Anticancer characteristics as well as other benefits of curcumin such as inhibition of tumor growth, autophagy activities, oxidative damage protection, and reduction of proliferation of tumor cells were confirmed. Conclusion: Curcuma longa can be used for the prevention and treatment of cancer, which generates new knowledge and different applications in the fight against this disease.